2010
DOI: 10.1002/ejoc.201000312
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Acylation of 1‐Adamantylacetic Acid in Trifluoroacetic Anhydride Medium: A Route to 2,4‐Bis(1‐adamantyl)acetoacetic Acid and Its Derivatives

Abstract: The self‐acylation of 1‐adamantylacetic acid (1) in trifluoroacetic anhydride, catalyzed by triflic acid, proceeds through the formation of the mixed 2,4‐bis(1‐adamantyl)acetoacetic–trifluoroacetic anhydride 2, and it was used as an efficient approach to previously unknown 2,4‐bis(1‐adamantyl)acetoacetic acid (3), its esters 4–6 and amides 7–11, and the sterically hindered 1‐adamantyl(1‐adamantylacetyl)ketene (12). The latter is stable in solution and can be isolated as a neat solid. Addition of methanol or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A process for the acylation of an indole derivative using Et 2 AlCl has been demonstrated on 3 kg scale, but these conditions were also not applicable to 6-azaindole 1 (Table , entry 2), providing only an approximately 19% conversion to acylated product 5 . Other reported procedures that utilized a combination of Grignard reagent and ZnCl 2 , 1,5-diazabicyclo[4.3.0]­non-5-ene (DBN), various Lewis acids, or a strong Brønsted acid, also performed poorly with our substrate (Table , entries 3–8). It has been reported that numerous electron-rich indole substrates can be acylated in the absence of pretreatments or catalysts; however, our substrate was again completely inert when subjected to these conditions (Table , entry 9) …”
Section: Resultsmentioning
confidence: 74%
“…A process for the acylation of an indole derivative using Et 2 AlCl has been demonstrated on 3 kg scale, but these conditions were also not applicable to 6-azaindole 1 (Table , entry 2), providing only an approximately 19% conversion to acylated product 5 . Other reported procedures that utilized a combination of Grignard reagent and ZnCl 2 , 1,5-diazabicyclo[4.3.0]­non-5-ene (DBN), various Lewis acids, or a strong Brønsted acid, also performed poorly with our substrate (Table , entries 3–8). It has been reported that numerous electron-rich indole substrates can be acylated in the absence of pretreatments or catalysts; however, our substrate was again completely inert when subjected to these conditions (Table , entry 9) …”
Section: Resultsmentioning
confidence: 74%
“…By acylation of 1-indanone ( 2a ) with (diphenylphosphoryl)acetic acid ( 1j ), the self-acylation of the acid 1j already occurred at room temperature, which complicated the separation of the desired dicarbonyl compound. When the acid 1j was heated under the conditions of TFAA/TfOH-mediated self-acylation of alkanoic acids recently reported by us [ 27 ] and decarboxylation was subsequently carried out, 1,3-diphenylphosphorylated acetone 5 could be obtained (reaction 2 in Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%